How to produce large sized microtubers of potato cv. Desiree - Magyar-Tábori, K.; Dobránszky, J. (International Journal of Horticultural Science, 2002)
In vitro tuberization was induced on explants with different number of nodes layered on a medium with high sucrose (8%) content: 30, 15, 10, 7 and 6 explants per jar were cultured containing 1, 2, 3, 4 or 5 nodes, respectively. Microtubers developed were graded by their smallest diameter, and the number of tubers per jar, their size distribution, their fresh weight and the multiplication rate were recorded. The highest multiplication rate (1.98) was obtained for explants with 5 nodes. The size distribution of tubers was markedly affected by treatments. The majority of microtubers (49.4%) were 6-8 mm in the case of the smallest explants (with I node). When explants with 2 to 5 nodes were used, the most microtubers were 8-10 mm but with an increase of explant size, more and more microtubers were produced with larger diameter up to 16 mm and average fresh weight of tubers also increased with the increase of explant size. For the microtuber production of Desiree the use of explants with two nodes can be suggested because in this treatment the average fresh weight of microtubers was high enough (250 mg) and the number of large sized microtubers was very high (79% was larger than 6 mm and 53% was larger than 8 mm).